Sparing confirmatory testing in primary aldosteronism (SCIPA): a multicenter retrospective diagnostic accuracy study - Albert Macaire C. Ong Lopez; Leo E. Tiu; Diana Collen Dimayuga; Oliver Allan C. Dampil; Erick S. Mendoza; Michael L. Villa; Andrea Marie Macabuag-Oliva (BMC Endocrine Disorders, 2024)
Abstract Background The diagnosis of primary aldosteronism (PA) is comprehensive, which includes case-detection testing, case confirmation followed by subtype classification. In certain instances, such as in the setting of spontaneous hypokalemia, suppressed renin activity (PRA) plus plasma aldosterone concentration (PAC) of > 15 ng/dL, one may not proceed with confirmatory tests. However, the quality of evidence behind this approach is very low. This study sought to evaluate the proposed “simplified confirmatory pathway” that can spare confirmatory testing for primary aldosteronism by evaluating the diagnostic performances of the various pre-specified PAC thresholds in combination with findings of suppressed renin and spontaneous hypokalemia. Methods This is a multi-center, retrospective diagnostic accuracy cohort-selected cross-sectional study. A total of 133 participants aged 18 years and above underwent saline infusion test between January 2010 to March 2024. The outcome measures comprise of the diagnostic performances of the different index test combinations (baseline PAC, baseline PRA and presence of spontaneous hypokalemia): sensitivity, specificity, negative predictive value, positive predictive value, positive likelihood ratio, negative likelihood ratio, and diagnostic accuracy. Data analysis was performed using SPSS 29.0.1.0 & MedCalc 20.218. Results Of the 133 patients who underwent saline infusion test, 88 (66.17%) were diagnosed with PA. A PAC of > 25 ng/dL plus PRA < 1.0 ng/dL/hr with spontaneous hypokalemia showed the highest specificity at 100% (95% CI 90.51%, 100.00%) and positive predictive value at 100% (85.18 – 100.00%). The minimum acceptable combination criteria were determined to be a PAC of > 20 ng/dL plus PRA < 0.6 ng/dL/hr, and presence of spontaneous hypokalemia. It has high specificity (94.59%; 95% CI 81.81%, 99.34%), positive predictive value (93.55%, 95% CI 78.49%, 98.29%), and moderate positive likelihood ratio (LR+) (6.39, 95% CI 1.61, 25.38) Conclusion A hypertensive patient with spontaneous hypokalemia and screening findings of PAC > 20 ng/dL and suppressed PRA of < 0.6 ng/ml/hr, may be classified as “overt primary aldosteronism confirmed” and may not need to proceed with dynamic confirmatory testing. Protocol registration number SRCTN34186253